2020
DOI: 10.1073/pnas.1919139117
|View full text |Cite
|
Sign up to set email alerts
|

Global diversity of microbial communities in marine sediment

Abstract: Microbial life in marine sediment contributes substantially to global biomass and is a crucial component of the Earth system. Subseafloor sediment includes both aerobic and anaerobic microbial ecosystems, which persist on very low fluxes of bioavailable energy over geologic time. However, the taxonomic diversity of the marine sedimentary microbial biome and the spatial distribution of that diversity have been poorly constrained on a global scale. We investigated 299 globally distributed sediment core samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
150
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(182 citation statements)
references
References 80 publications
21
150
1
Order By: Relevance
“…The superficial sediments (≤ 10 centimeters in depth) were collected using a box corer (Figure 2). The observed taxonomy was diverse, as previously reported (Hoshino et al, 2020); however, similar to sediments from oil-polluted sites (Head et al, 2006), hydrocarbon degraders were also abundant in our samples. Sequencing reflects the presence of bacteria and archaea; however, because we were focused on collecting bacteria, the relative abundance was greater.…”
Section: Bacterial Taxonomy In the Sediments From The Southern Gomsupporting
confidence: 87%
“…The superficial sediments (≤ 10 centimeters in depth) were collected using a box corer (Figure 2). The observed taxonomy was diverse, as previously reported (Hoshino et al, 2020); however, similar to sediments from oil-polluted sites (Head et al, 2006), hydrocarbon degraders were also abundant in our samples. Sequencing reflects the presence of bacteria and archaea; however, because we were focused on collecting bacteria, the relative abundance was greater.…”
Section: Bacterial Taxonomy In the Sediments From The Southern Gomsupporting
confidence: 87%
“…This indicates that relatively deep sequencing is needed to capture the microbial diversity present in these complex communities. A recent study comparing global diversity of marine sediments detected over 34,000 ASVs associated with bacteria and archaea across 299 sites (Hoshino et al, 2020). In total, our study found over 27,000 ASVs from CD and CI samples around Carrie Bow Cay, Belize.…”
Section: Discussionmentioning
confidence: 56%
“…Lokiarchaeota belongs to a recently discovered superphylum Asgardarchaeota, which is a hot topic linked to the origin of eukaryotes (Spang et al 2018). To date, candidate species of Lokiarchaeota were universally found near deep sea hydrothermal vents and marine sediments (Spang et al 2015, Spang et al 2018, Hoshino et al 2020, Wong et al 2020, Yin et al 2020). A recent study has found candidate Lokiarchaeota present in hypersaline lakes near Black Sea (Bulzu et al 2019), whereas our study highlighted the first time that Loki-2 species were found from deep-inland hypersaline lake sediments.…”
Section: Discussionmentioning
confidence: 99%
“…As such environmental parameters (physical, chemical and biological) have direct and indirect effect on microbial communities (Berdjeb et al 2011, Nishiyama et al 2018, Easson and Lopez 2019, Glasl et al 2019), exploring uncommon environment can expand the breadth of our understanding on microbial diversity and potential functions. A few studies have already launched targeting rarely explored environments on deserts (Finstad et al 2017), oil fields (Eze et al 2020), hydrothermal vents (Anderson et al 2017) and non-marine soda lakes (Vavourakis et al 2018), but such number of investigations were still scarce to support the expansion of microbial diversity, compare to a vast majority of studies on marine, soil and human-associated microbiomes (Hoshino et al 2020, Nascimento Lemos et al 2020, Almeida et al 2021).…”
Section: Introductionmentioning
confidence: 99%